Penilaian Penggunaan Framework COBIT 2019 dalam Pengelolaan Teknologi Informasi Pada Institusi Perguruan Tinggi - Anadya Tafdhilla; Hasna Iftinan, Jihan; Azzahra Rahmadani; Anita Wulansari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Information Technology Governance plays a very important role in managing all company needs. Especially in the world of education, technology plays a very important role in carrying out the vision and mission of all educational service needs. However, there are many problems experienced and the order of infrastructure and how to manage it that is not maximized so that it makes the order not run well. Because this can lead to various problems from the course of the education service process. Therefore, a framework such as COBIT 2019 is needed which has become the main guideline in improving the effectiveness and efficiency of information technology management in various organizations, including universities. This journal aims to assess COBIT 2019 framework users at various higher education institutions to determine the level of capability and gaps that generally occur. Through a Systematic Literature (SLR) approach, the journal details a number of significant findings, including an in-depth understanding of how COBIT 2019 is adopted and implemented in higher education settings. With Research Question (RQ) i.e. RQ1 Which domains in IT Governance are the main focus for most colleges and high schools implementing the COBIT 2019 framework, RQ2 What are the capability levels and advice provided in most higher education institutions implementing the COBIT 2019 framework. The results of this study found 13 articles that met the inclusion criteria, after identifying titles, abstracts, and conclusions from 48 articles that fell into the exclusion criteria. From the screening of these journals, the results show that the main focus of universities and colleges in implementing the COBIT 2019 framework is on the DSS05 domain. In many higher education institutions that implement the COBIT 2019 framework, the level of capability tends to depend on a strong understanding of best practices in managing IT operations, because there are many universities that have not been able to achieve the desired capability targets. As such, these institutions are required to continuously improve their capabilities in the face of dynamic IT environment changes and strengthen efforts to maintain the resilience of their operational systems.